ZINC AND COPPER SORPTION IN THE AFFECTED SOILS OF THE CHEREPOVETS METALLURGICAL COMPLEX - O. Rogova; Yu. Vodyanitsky (Бюллетень Почвенного института им. В.В. Докучаева, 2010)
The laws of zinc and copper absorption by agrarian and carbonate soils in the area of Cherepovets Steel Mill are described. Sorption isotherms demonstrate high affinity of PPK of the studied soils to zinc and copper. Approximation of experimentally obtained isotherms by three methods: Freindlich, Lengmyur, Dabinin-Radushkevich. It is shown that Langmur's model cannot to be applied to most isotherms. The Dibininin model -Raduskevich well approximates the obtained data and enables thermodynamic characteristics of the adsorption process. According to the obtained indicators, the most significant contribution to sorption processes is made by minerals of iron oxides and hydroxides. Coefficients of approximation of isotherms of adsorption by different equations are analyzed. It is recommended to use the Dibininin-Radushkevich equation when the equation Langemura is inapplicable.